Snack Business Development Strategy Using the Canvas Model Business Approach at UD Mentari Jaya Putra, Tanggul District, Jember District - Tarigan, Rallyanta (Jurnal Bisnis Mahasiswa, 2025)
Business competition is currently increasing, companies must improve their business capabilities so that their businesses can develop and compete with other companies. Therefore, companies must have a strategy so that their business continues to run and develop. Research on "Snack Business Development Strategy Using the Business Model Canvas Approach at UD. Mentari Jaya Putra, Tanggul District, Jember Regency" uses a qualitative descriptive research type. Qualitative descriptive research was carried out to describe the actual situation of the UD snack business environment. Mentari Jaya Putra. The first step in the descriptive analysis carried out in the research was to formulate the UD business model. Mentari Jaya Putra in its current snack business uses the Business Model Canvas approach. The second step is to formulate improvements to the new business model with the results of previously obtained data so that a business model is created that is suitable for the business development strategy at UD. Mentari Jaya Putra. The formulation of the Business Model Canvas through 9 BMC components, each of which is analyzed, then separated again into the right (efficiency side) and left (value side) components consisting of customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure.